Design and development of a versatile ice clamping system - Bahar, Rubina; Yahya, Nur Adilah; Ariff, Tasnim Firdaus (Trans Tech Publications Ltd., Switzerland, 2015)
In manufacturing industries, workpiece clamping is one of the basic requirement prior to machining process as the clamping system is responsible to maintain the workpiece rigidity and withstand the cutting force generated from the machining process. Besides, Clamping device is one of the reasons which influence the surface integrity of a part. Clamping workpieces for machining can be challenging especially for intricate non-symmetric geometry and vulnerable parts. In this study, a new system has been designed and developed where the workpiece is submerged in a fluid and the fluid is completely frozen to form ice that holds the workpiece rigidly. This ice clamping system can hold any parts of the workpiece regardless of their geometry and fragility. To freeze the desired workpiece, the energy required for 942 cm3 of clamping fluid was 98.43 kJ. Total freezing time was 90 minutes. Further development on the system is required in terms of improving freezing time and de-freezing of the work-piece.